The Message is on the Wall? Emotions, Social Media and the Dynamics of Institutional Complexity - Toubiana, Madeline; Zietsma, Charlene (Academy of Management Journal, 2017)
In this paper, we explore how emotions influence organizations in situations of institutional complexity. In particular, we study members’ and leaders’ emotive responses and influence activities in response to a disruptive event that led to a violation of expectations. Our findings show that when people’s expectations of an organization’s actions are violated it can trigger a process of emotional escalation that leads to destabilization of the organization through the emotion-laden influence activities of shaming and shunning. The violation in our case resulted in strong negative emotions expressed on Facebook. Facebook acted as an emotional echo chamber where negative emotions were amplified and led to members’ emotion-driven influence activities, eventually triggering regret and adaptation by the organization. We discuss implications for the study of emotions in institutional dynamics.